177k views
0 votes
Solve the following logarithmic equations.
ln(32x^2) − 3 ln(2) = 3

User Yifei
by
5.3k points

1 Answer

3 votes

Answer:


x=\pm \frac{\sqrt{e^(3) } }{2}

Explanation:

Rewrite the equation using the next propierties:


log((1)/(x) )=-log(x)


ylog(x)=log(x^(y) )


log(x*y)=log(x)+log(y)


ln(32x^(2) )-ln(2^(3))=3\\ ln(32x^(2) )+ln((1)/(2^(3) ) )=3\\ln((32x^(2) )/(8))=3\\ ln(4x^(2) )=3

Cancel logarithms by taking exp of both sides:


e^{ln(4x^(2)) } =e^(3) \\4x^(2) =e^(3)

Divide both sides by 4:


x^(2) =(e^(3) )/(4)

Take the square root of both sides:


x=\pm \sqrt{(e^(3) )/(4) } =\pm \frac{\sqrt{e^(3) } }{2}

User Leowang
by
5.8k points